Estetika Iklan Shopee 12.12 Birthday Sale Versi Blackpink - Aisyah, Chairini; Handriyotopo, Handriyotopo (Serat Rupa: Journal of Design, 2023)
Shopee is one of the most well-known electronic trading stages for Indonesians, particularly youngsters today. Shopee advances deals stage through promoting media airs on TV channels. One of Shopee's commercials utilizing brand ambassador is the Korean Pop symbol, Blackpink. The utilization of brand ambassador in each advancement did by Shopee can associate publicists to purchasers at specific occasions. Text studies with clear portrayals are the focal point of this subjective exploration approach utilizing the Applied Media Style approach by zeroing in on the media parts that structure promotions. This study will concentrate on Applied Media Aesthetics' division of light and color, two-dimensional and three-dimensional space, time and movement, and sound. This study aims to examine the aesthetics of a commercial advertising program, particularly the Blackpink version of the Shopee 12.12 Birthday Sale, which celebrates the sale's anniversary on the 12th day of the 12th month each year. The aftereffects of the review are through uncovering the stylish worth of the visual commercial Shopee 12.12 Birthday Deal adaptation of Blackpink and giving data to general society about the presence of these promotions.